Spectrum of metastatic tumours to orbit over the last twenty years in a tertiary care eye hospital-A retrospective study - Tahir, Faizan; Tayyab Afghani; Saadullah Ahmad; Amna Manzoor; Fariha Taimur; Sumeya Ali Khan; Muhammad Saad (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the type and presentation patterns of tumours metastasising to orbit. Method: The retrospective study was conducted at the Al Shifa Trust Eye Hospital, Rawalpindi, Pakistan, and comprised data of all patients with orbital metastatic lesions over a 20-year period, from January 1, 2004, to December 31, 2023. Data was analysed using SPSS 22. Results: Of the 30 patients, 17(56.7%) were males and 13(43.3%) were females. The highest incidence of orbital metastatic disease was among those aged <10 years 9(30%) and >60 years 11(36.7%). Roof was the commonest site of involvement within the orbit 13(43.3%). Proptosis was the main feature at presentation. Diagnosis was made clinically in 14(46.7%) patients and histologically in 16(53.3%). All the 30(100%) cases were referred to the oncology service for further management. Of them, 2(6.7%) patients were lost to follow-up, 20(66.7%) died within one year of diagnosis, and 8 (26.6%) patients were still under treatment. Conclusion: The diagnosis of orbital metastasis should always be considered for orbital lesions in all age groups, especially in patients with a known cancer elsewhere. Orbital metastasis usually becomes evident at an advanced stage of underlying malignancy, leading to a high mortality rate. Key Words: Orbital metastasis, Orbital tumours, Orbital malignancies.